Research advances of the drift reducing technologies in application of agricultural aviation spraying - Chen, Shengde; Lan, Yubin; Zhou, Zhiyan; Deng, Xiaoling; Wang, Juan (International Journal of Agricultural and Biological Engineering, 2021)
With the gradual deterioration of the ecological environment and the increase in requirements for the quality of modern life, the use of pesticides is bound to develop towards higher pesticide utilization and less environmental pollution, and the low-volume spraying for agricultural aviation operation combined with the Drift Reducing Technologies (DRTs) may be a useful way to achieve this goal. Based on an analysis of the spray drift mechanism and the primary factors influencing aerial spraying, previous research on DRTs in aerial spraying were reviewed and summarized, and it was found that DRTs in aerial spraying can effectively reduce the environmental pollution caused by pesticide drift by reducing the spraying amount of pesticides and improving the control effect of pesticides, included aerial electrostatic spray technology, aerial spray adjuvant, aerial air-assisted spray technology, drift reducing nozzles and aerial variable-rate spray technology. And according to the analysis of the current research status, some suggestions and countermeasures to reduce droplet drift of agricultural aviation spraying were put forward from the aspects of strengthening the research on DRTs for plant protection Unmanned Aerial Vehicle (UAV) and adopting reasonable DRTs methods. It is hoped that provide reference and guidance for the enterprises’ product improvement and users’ practical operation, and play the advantages of precision agricultural aviation spraying fully.Keywords: agricultural aviation spraying, pesticide, drift, DRTs, precision agricultureDOI: 10.25165/j.ijabe.20211405.6225Citation: Chen S D, Lan Y B, Zhou Z Y, Deng X L, Wang J. Research advances of the drift reducing technologies in application of agricultural aviation spraying. Int J Agric & Biol Eng, 2021; 14(5): 1–10.